A kinetic and Kinematic analysis in two assessment situation with bench press. Free Weight vs Smith Machine. Project pilot. - I. J. Bautista; I. J. Chirosa; J. Arguelles; J. M. Monje; L. J. Chirosa (Federación Extremeña de Balonmano; University of Extremadura, 2012)
This pilot study examines the most relevant kinetic and kinematics variables in two bench press exercises; Smith Machine (PMS) vs. free weights (PBL). Two trained subjects participated in the research following informed consent. To determine the maximum load (1-RM), two incremental protocols were used for PMS and PBL. Subject 1 (S-1) produced force values of 770N and 837N, peak force of 28ms and 12ms, in PBL and PMS respectively. Values for subject 2 (S-2) were 693N and 849N, PMF of 60ms and 66ms for PBL and PMS respectively. Detailed analyses of the following variables were performed; velocity curves for each load, the "sticking period", the distances of grip width, and changes in bar inclination during the ascent phase of the lift were examined. The key findings of this research, and the basis for future research demonstrate that PBL is recommended as a training exercise, while more reliable information regarding force variables can be attained through using PMS in measurement sessions. Key Words: Bench Press, smith machine, free weight, strength assessment, upper limb.